Happiness and Gold Prices - Hans Byström (Lund University, School of Economics and Management, Department of Economics, 2020)
We use the Twitter-based Hedonometer happiness index to study the link between happiness and gold price changes. We find no significant correlation between the two when we look at correlations across the entire distributions. However, turning to an extreme value theory (EVT) modeling of the tails of the non-normally distributed happiness distribution we find that during particularly depressing days the gold price often goes up. In a sense, gold is found to serve as a happiness-related safe haven, i.e. as a hedge against extreme unhappiness.
Keywords: D83; G14; G41; G50; 330; Twitter; happiness; Hedonometer; gold price; tail; extreme value theory